ANALISIS PEMANFAATAN LINGKUNGAN SEKOLAH DALAM PROSES PEMBELAJARAN EKONOMI KELAS XI IPS SMA ST.FRANSISKUS ASISI - Fransiska Uli; Warneri Warneri; Husni Syahrudin (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2019)
AbstractThis study aims to determine the utilization of the school environment in the learning process of Economy class XI IPS Private High School St. Fransiskus Asisi North Pontianak. This research is based on the findings of the problame when the researcher made observations regarding the use of the school envinormnet conducted by teachers and students during the learning process. The research method used is descriptive method with qualitative approaches and forms of survey research. The data sources in this study were students of class XI IPS which consisted of 4 classes with 20 students as representatives of representatives conducting interview and forgiving teachers in Economics subjects. Data collection was obtained through observation guidelines and interview guidelines, then analyzed using data reductio, data presentation, and verification/conclusion drawing, then checking the validity of the data using triangulation techniques. Researchers conducted research research 6 times, namely by conducting research observations as much as 4 times and interview as much as 2 days. The result show that the utilization of the school environment with the type of natural (physical) which consist of aspects of classrooms, buildings, librraries, class facilities, textbooks and media/tools such as projectors are good enough, in the aspect of air ventilation, space lighting class, and the size of the classroom is still not good because most of the students feel that the classroom is not enough to make them free in their activities. While the type of  social environment in the aspect of teacher relations eith students already looks quite good but the relationship between students and students is said to be still not good, due to the selfishness that is still visible from each student.Keywords: Utilizations of the School Environment, Economic Learning